The Effect of Consumption Values on Continued Usage Intention Moderated by Gender on the Go-Food Application in Padang City - Ananda, Gunawan; Patrisia, Dina (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study examines the factors that influence the intention to continue using the Go-Food application in Padang City, focusing on the role of functional value, social value, emotional value, conditional value, epistemic value and gender as moderation. This study aims to determine the effect of consumption values on continued usage intentions, and test the moderating role of gender in the relationship. The sample used was 320 respondents. The data were processed using SmartPLS and collected through an online questionnaire. The results showed that (1) Functional Value has a positive and significant effect on Continued Usage Intention in Go-Food users. (2) Social Value has no significant effect on Continued Usage Intention in Go-Food users. (3) Emotional Value has a positive and significant effect on Continued Usage Intention in Go-Food users. (4) Conditional Value has a positive and significant effect on Continued Usage Intention in Go-Food users. (5) Epistemic Value has a positive and significant effect on Continued Usage Intention in Go-Food users, and gender moderates the influence of several value variables (Functional Value, Emotional Value, Conditional Value, and Epistemic Value) on Continued Usage Intention at Go-Food, but does not moderate the influence of Social Value. Gender tends to strengthen the influence of emotional and epistemic aspects on women, while functional and conditional values have more influence on men.